Cytogenetic Effects of Gamma Rays on Indica Rice Radha-4 - Basi, S; Subedi, LP; KC, GB; Adhikari, NR (Journal of the Institute of Agriculture and Animal Science, 2006)
The present study was conducted to understand the effects of different doses of radiations by gamma rays of Co60 on cytogenetics of indica rice, Radha-4 at the Central Lab, Institute of Agriculture and Animal Science, Rampur, Nepal. The immature PMC of M1 generation plants were analyzed performing the usual smearing and squashing technique. Radiation had a significant effect causing different types of cytogenetic aberrations, such as univalent and multivalent association of chromosomes, chromatin-bridges, laggards, fragments, stickiness, and multinucleated cells. An increasing number of aberrant cells with increasing dose of radiation was identified. The greatest share of aberration was identified due to multivalent association as a result of translocation followed by bridges and laggards, and the least effect for the stickiness of the chromosomes. Finally, 35 KR doses of gamma rays was the most potent dose inducing cytogenetic aberrations in meiotic pollen mother cell of rice compared to other dose spectrum. J. Inst. Agric. Anim. Sci. 27:25-36 (2006)